Search for gamma-ray spectral lines from dark matter annihilation in dwarf galaxies with the High-Altitude Water Cherenkov observatory - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; et al. (Physical Review D, 2020)
Local dwarf spheroidal galaxies (dSphs) are nearby dark-matter dominated systems, making them excellent targets for searching for gamma rays from particle dark matter interactions. If dark matter annihilates or decays directly into two gamma rays (or a gamma ray and a neutral particle), a monochromatic spectral line is created. At TeV energies, no other process is predicted to produce spectral lines, making this a very clean indirect dark matter search channel. With the development of event-by event energy reconstruction, we can now search for spectral lines with the High Altitude Water Cherenkov (HAWC) Observatory. HAWC is a wide field of view survey instrument located in central Mexico that observes gamma rays from similar to 200 GeV to similar to 200 TeV. In this work we present results from a recent search for spectral lines from local, dark matter dominated, dwarf galaxies using 1038 days of HAWC data. We also present updated limits on several continuum channels that were reported in a previous publication. Our gamma-ray spectral line limits are the most constraining obtained so far from 20 TeV to 100 TeV.
CRIS-Team WoS Importer:2020-05-15